A spiritual inheritance? Family spirit, virtue and vocation in the Vies of the Lamoignon dévots. (26th August 2020) - Forrestal, Alison
Abstract: Members of the Parisian robe Lamoignon family were among the most prominent dévots of the French Catholic Reformation. This article explores the family's religious engagement through six substantial biographies or vies written by close relatives between 1663 and 1688–90, which reflected on the devotional lives of Chrétien and Marie Lamoignon and three of their four children, Guillaume, Anne and Madeleine. It analyses how the authors adopted the popular strategy of life-writing to recall, reflect on and interpret the significance of their religious choices and experiences for themselves and for the family as a whole. Appraisal of their habits became building blocks for the construction of what the authors defined as a Lamoignon 'family spirit', which included a rhetoric of humility that was designed to withstand pride, deflect accusations of venality, validate the family's advancement and inflect their history with a cohesive spiritual identity.